2022
DOI: 10.1080/87559129.2021.2012795
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Barriers for Commercial Uptake of Edible Coatings for Fresh Fruits and Vegetables Industry- A Review

Abstract: As the world population is expected to rise to nearly eleven billion by 2050, a concomitant rise in the demand for fresh fruits and vegetables (FFV) is expected. FFV are highly perishable and constitute 20% of the global food wastage with nearly 30% of the losses occurring at the postharvest (PH) phase. This represents a challenge to ensure food and nutrition security for future generations. A proposed solution is the use of edible coatings incorporating natural ingredients that have the potential to reduce PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 197 publications
0
7
0
Order By: Relevance
“…238 In the US, most polysaccharides including xanthan gum that are used as major components in edible coatings are approved by the FDA. 235 Chitosan/tannic acid/ corn starch bilayer films showed reduced WVP compared with chitosan film, and coating of these bilayer films on banana improved its storage time from 3 to 6 days. 239 However, tannic acid sensitivity to pH, light, and oxidation can cause a migration issue from the film.…”
Section: Food Safety Consideration In Coating Technology (Migration I...mentioning
confidence: 91%
See 4 more Smart Citations
“…238 In the US, most polysaccharides including xanthan gum that are used as major components in edible coatings are approved by the FDA. 235 Chitosan/tannic acid/ corn starch bilayer films showed reduced WVP compared with chitosan film, and coating of these bilayer films on banana improved its storage time from 3 to 6 days. 239 However, tannic acid sensitivity to pH, light, and oxidation can cause a migration issue from the film.…”
Section: Food Safety Consideration In Coating Technology (Migration I...mentioning
confidence: 91%
“…235 A recent survey on the consumer perception of FFV with edible coatings showed that 79.3% of the respondents would buy edible-coated FFV if it is approved by the FDA. 235,236 For example, there are super hydrophobic edible coatings produced from FDA-approved (as generally recognized as safe (GRAS)) carnauba wax and beeswax for application on food containers to easily remove liquid food. 237 Xanthan gum-based coating on fresh cut lemon increased the storage time (at 4 °C) to 21 days.…”
Section: Food Safety Consideration In Coating Technology (Migration I...mentioning
confidence: 99%
See 3 more Smart Citations